The Overview Of Pregnant Women's Knowledge Regarding Hepatitis B Prevention Efforts In Newborns In Surabaya City - Noorlaila Ainunnissa; Dewi Setyowati; Budi Prasetyo (International Journal Of Health Science, 2024)
In 2022, 50,744 pregnant women were diagnosed with Hepatitis B, and 35,757 babies were born to infected mothers. Despite the majority of babies receiving HB0 and HBIg immunizations within 24 hours, 135 babies tested positive for Hepatitis B at 9-12 months of age. Maternal knowledge influenced the prevention behavior of transmitting Hepatitis B to infants. This study examines pregnant women's Hepatitis B prevention knowledge in Surabaya, analyzing factors like age, information, education, and gravid status. This research in Surabaya involved 115 respondents, utilizing a quantitative cross-sectional method at Tanah Kali Kedinding and Kalirungkut Health Centers from March to November 2023. Sampling was done through consecutive sampling, and knowledge was assessed using a questionnaire, analyzed through the Spearman statistical test. The study revealed that 72.2% of respondents had good knowledge about preventing Hepatitis B transmission to newborns. Bivariate tests showed a non-significant relationship between age and knowledge (p=0.290), while the relationship between information sources (p=0.02), last educational level (p=0.315), and gravid status (p=0.052) were significant. In conclusion, most respondents demonstrated good knowledge, and there was a correlation between information sources and knowledge, while age, last educational level, and gravid status did not significantly correlate with respondents' knowledge.